Endothelial Progenitor Cells and Vascular Alterations in Alzheimer’s Disease - Custodia, Antía; Ouro, Alberto; Romaus-Sanjurjo, Daniel; Pías-Peleteiro, Juan Manuel; de Vries, Helga E.; Castillo, José; Sobrino, Tomás (Frontiers in Aging Neuroscience, 2022)
Alzheimer's disease (AD) is a neurodegenerative disease representing the most common cause of dementia worldwide. The early diagnosis of AD is very difficult to achieve due to its complexity and the practically unknown etiology. Therefore, this is one of the greatest challenges in the field in order to develop an accurate therapy. Within the different etiological hypotheses proposed for AD, we will focus on the two-hit vascular hypothesis and vascular alterations occurring in the disease. According to this hypothesis, the accumulation of β-amyloid protein in the brain starts as a consequence of damage in the cerebral vasculature. Given that there are several vascular and angiogenic alterations in AD, and that endothelial progenitor cells (EPCs) play a key role in endothelial repair processes, the study of EPCs in AD may be relevant to the disease etiology and perhaps a biomarker and/or therapeutic target. This review focuses on the involvement of endothelial dysfunction in the onset and progression of AD with special emphasis on EPCs as a biomarker and potential therapeutic target.